Using empirical evidence generated by Holt’s linear method to inform HIV programming in Brazil - Dr. Smartson. P. NYONI; Thabani NYONI (Zien Journals, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Brazil from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s linear method (HLM). The optimal values of smoothing constants α and β are 0.4 and 0.1 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will generally maintain an upward trend over the out of sample period. Therefore, we encourage authorities to scale up educational campaigns among the sexually active age group with particular emphasis on HIV prevention strategies such as correct and consistent use of condoms, behavior change, PrEP and voluntary medical male circumcision.
Keywords: Exponential smoothing; Forecasting